A survey on Wi-Fi signal based identification technology - Zhongcheng WEI; Xinqiu ZHANG; Bin LIAN; Wei WANG; Jijun ZHAO (物联网学报)
With the constant progress of the information technology, the research on identification is developing towards unawareness and automation, and applied widely in many fields, such as human-computer interaction, smart home and intelligent security.As a non-contact wireless sensing technology, Wi-Fi signal based identification is progressively evolving towards the directions of multi-attribute identification and legality verification.Firstly, the principle of wireless signal-based identification was introduced, and reviews pretreatment processes from the viewpoint of signal processing were reviewed.Then, identification implementation was discussed from two different bases of walking and daily activities.Two major development trends of identification which were multi-attribute identification and legality verification were discussed from function evolution’s views.Finally, the multiple research areas were indicated including hyper-level feature extraction, daily activities’ analysis, identification model construction, and multi-technology fusion as future directions of realizing more robust, diversify and universal identification, which would provide the important support for the research and development of Internet of things perception layer.